Lipoid proteinosis: A review with two case reports - Vishal Kabre; Smitha Rani; Keerthilatha M Pai; Sakshi Kamra (Wolters Kluwer Medknow Publications, 2015)
Lipoid proteinosis (LP) is a rare autosomal recessive genodermatoses characterized by deposition of amorphous hyaline material in different parts of the body, especially the skin, mucous membranes of the upper aerodigestive tract, and internal organs. Oral cavity is most extensively affected area by the disease. This paper reports two classic cases of LP with oral manifestations but without a history of consanguinity along with a concise review of the literature on the disease.